PERANCANGAN APLIKASI PENYANDIAN TEKS DENGAN METODE MULTIPLE XOR - Simorangkir, Holder (JIK: Jurnal Ilmu Komputer, 2018)
Many hackers who want to destroy or retrieve data or important information from the company, data or information taken can be useful for others or damage the order of information owned company so as to make the company become problematic. Storage of data or information is necessary and far from the reach of hackers. Encryption is one of the efforts made to obscure the stored text so that the company can avoid the destruction. Frequently used method is MD5, RSA, DES, Symmetric Stream Chipper method, and on this problem used Multiple XOR method with 32 bit. The result of this encryption makes the information into a combination of alphabetically coupled with Greek alphabetics making the hackers have to work and learn more to get results to be chipper text made.Ã‚Â Keywords : Encryption, Multiple XOR,Hackers